The impact of 9/11 on us reit returns: Fundamental or financial? - Gheno, Andrea; Lee, Stephen L. (International Journal of Strategic Property Management, 2010)
Following the attack on the World Trade Center on 9/11 volatility of daily returns of the US stock market rose sharply. This increase in volatility may reflect fundamental changes in the economic determinants of prices such as expected earnings, interest rates, real growth and inflation. Alternatively, the increase in volatility may simply reflect the effects of increased uncertainty in the financial markets. This study therefore sets out to determine if the effects of the attack on the World Trade Center on 9/11 had a fundamental or purely financial impact on US real estate returns. In order to do this we compare pre‐and post‐9/11 crisis returns for a number of US REIT indexes and in general we find that the effect of the attack on the World Trade Center on 9/11 had only a financial effect on REIT returns and therefore was transitory. First Published Online: 18 Oct 2010